Aortic Valvuloplasty as Bridging for TAVI in High-Risk Patients with Heyde’s Syndrome: A Case Report - Cosmo Godino; Anna Giulia Pavon; Antonio Mangieri; Alberto Margonato (Case Reports in Medicine)
There is a frequent association between aortic valve stenosis and gastrointestinal bleeding, also known as Heyde’s syndrome. In these patients, the aortic valve replacement should be recommended as “gold standard.” In high-surgical-risk patients, the Transcatheter Aortic Valve Implantation (TAVI) is an alternative option. However, the risk of bleeding recurrence, related to double antiplatelet therapy started after TAVI, cannot be excluded especially in the first months. We present a case of a patient with a severe aortic valve stenosis and a history of previously documented angiodysplasia and recurrence of gastrointestinal bleeding initially treated only with balloon aortic valvuloplasty that excluded recurrence of bleeding during the subsequent six months of followup. Therefore, a definite transfemoral Edwards XT valve implantation was planned to be performed in case of recurrence of aortic stenosis.